PERAN BUDAYA ORGANISASI DALAM MENDUKUNG IMPLEMENTASI MANAJEMEN STRATEGIS DI RUMAH SAKIT: TINJAUAN LITERATUR THE ROLE OF ORGANIZATIONAL CULTURE IN SUPPORTING THE IMPLEMENTATION OF STRATEGIC MANAGEMENT IN HOSPITALS: A LITERATURE REVIEW - Erick Juniyantho Wijaya; Latesia Pramagistra Nurshabrina; Grace Bambulu; Purwadhi Purwadhi; Yani Restiani Widjaja (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2026)
Organizational culture is a key factor that plays a crucial role in supporting the successful implementation of strategic management in hospitals. Amid increasing demands for service quality, regulatory changes, and intensifying competition in the healthcare industry, hospitals are required not only to formulate appropriate strategies but also to ensure that these strategies are effectively implemented by all organizational elements. This study aims to systematically examine the role of organizational culture in supporting the implementation of strategic management in hospitals through a Systematic Literature Review (SLR) approach. The research method involved identifying relevant scientific articles from Google Scholar, Scopus, PubMed, and ScienceDirect databases, covering publications from 2020 to 2025. The literature selection process followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, with inclusion criteria focusing on studies addressing organizational culture, strategic management, and hospital settings. The selected articles were analyzed using a thematic analysis approach to identify patterns, roles, and mechanisms through which organizational culture supports strategy implementation. The findings indicate that a strong, adaptive organizational culture aligned with the hospital’s strategic vision enhances employee commitment, strengthens strategic communication, fosters innovation, and supports organizational sustainability. Therefore, strategic management of organizational culture is a critical determinant of successful strategic management implementation in hospitals.